Penerapan Metode Qawāid Wa Tarjamah Untuk Meningkatkan Kemampuan Siswa Dalam Memahami Mabni dan Mu’rāb Pada Struktur Bahasa Arab - Nasrul Waton; A Hadi Setiawan; Angger Putri M (Al Mitsali, 2022)
This research is based on the difficulty of grade VIII F Ubay bin Ka'ab SMP Qur'an Darul Fattah students in understanding Arabic language material, especially mabni and mu'rāb material contained in the Arabic language structure. The purpose of this study was to improve students' understanding of Arabic rules, especially mabni and mu'rāb. The method that the researchers used was Qawāid Wa Tarjamah which the researchers conveyed directly to the students in the class. The subjects the researcher aimed at were 20 students of grade VIII SMP Qur'an Darul Fattah. The type of research used is qualitative.